(untitled) (Journal of Partial Differential Equations, 1992)
In this paper the author considers the initial boundary value problems for the system of Zakharov equtations (Za) and for the system of complex-Schr&#246dinger-real-Boussinesq equations (SBq) in a two-dimensional domain. He proves the global existence and uniqueness of smooth solutions of (SBq) and of (Za) by means of continuous extension method and a priori estilmates.